Nutritional composition of unripe and ripe freeze-dried Terung Asam from Sarawak - Hwong, Chia-Shing; Koh, Chen-Chung; Hii, Siew-Ling (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aimed to assess and compare the nutritional composition between unripe and ripe freeze-dried Terung Asam from Sarawak. Terung Asam was checked for its maturity upon collection. Whole fruits were freeze-dried and used for proximate analyses. The redness/greeness (a*) of unripe and ripe fresh Terung Asam used in this study were -14.20 ± 3.11 and 12.57 ± 1.60 respectively. The moisture content of unripe fresh Terung Asam was significantly higher than ripe fresh Terung Asam (p < 0.05). There were statistically significant differences in crude protein (p < 0.05), crude fat (p < 0.05), ash (p < 0.05) and crude fibre (p < 0.001) between unripe and ripe freeze-dried Terung Asam (UFTA and RFTA respectively). RFTA had higher crude fibre (19.87 ± 0.68g/100g) and ash (6.20 ± 0.18g/100g) than UFTA (13.86 ± 0.58g/100g crude fibre, 5.43 ± 0.12g/100g ash). In contrast, UFTA was higher in protein (10.77 ± 0.30g/100g) and fat (0.74 ± 0.05g/100g) than RFTA (9.43 ± 0.40g/100g crude protein, 0.48 ± 0.08g/100g fat). The results of this study suggested that whole fruits of UFTA and RFTA were good source of crude protein, crude fibre and mineral. The data gathered from this research can contribute to the body of knowledge of this underutilized indigenous fruit as well as becoming useful for future product development using Terung Asam.